T.1 - Tố Hữu; Hà Minh Đức (H., 2009)
Giới thiệu các tập thơ của Tố Hữu như: Từ ấy, Việt Bắc, gió lộng, ra trận, máu và hoa, một tiếng đờn, ta với ta
Keywords: Tố Hữu, -- 1920-2002; Văn học Việt Nam -- Thơ